Improving the Quality of Memorization by Using the Al Jazi Method in Class IX Students at Mafatih Boarding School - Putra Raihan Nur Alam; Imam Tabroni; Uwe Barroso; Amina Intes (Yayasan Adra Karima Hubbi, 2023)
Background. This study aims to determine the application of the Al-Jazi method in improving the quality of Santri memorization. The place of research was at Pesantren Mafatih Wanayasa school. Purpose. The main data sources are Tahfidz Coordinator, Muhafizh Tahfidz and 9th grade students of Pesantren Mafatih Wanayasa. Method. . This research was motivated by the Al-Jazi method program implemented at Ponepes Mafatih Wanayasa. Muhafizh provides a special method so that students do not feel bored when memorizing the Qur'an. The method applied is the Al-Jazi method to train Santri in repeating memorization. The Al-Jazi method is a way to facilitate memorization and sharpen memorization. Results. This research method uses Classroom Action Research. Data collection techniques with observation, and documentation. The data analysis used is data reduction, data display (data presentation), and decision making. Conclusion. The results of this study indicate that the implementation of the Al-Jazi program is very useful and capable of improving the quality of Santri memorization. Although there are many obstacles at the technical level, with the Al-Jazi program, Santri can be istiqamah in reviewing their memorization, either memorizing new material or memorizing old material.